The Effect of Team Games Tournament Learning Model on Visual Spatial Ability Early Childhood - Rosalia Mustika Soares Lemos; I Made Elia Cahaya; Ni Made Ayu Suryaningsih (Educare: Journal Educational and Multimedia, 2025)
Visual-spatial ability is one of the important aspects in the cognitive development of early childhood, which plays a role in understanding shape, size, position, and spatial relationships. This study aims to analyze the effect of the Team Games Tournament (TGT) learning model on the visual-spatial abilities of early childhood. The TGT learning model was chosen because it is based on group games that require children to collaborate, solve problems, and hone visual-spatial skills through media such as puzzles, blocks, sizes, and directions. This research is an experimental research, namely Quasi experimental design. The design used is Non-Equivalent Control Group Design. Data collection using observation, interview and documentation methods. The subjects of this study were Group B of Satya Dharma Kindergarten consisting of control class and experimental class. The data analysis results show tcount = 2.323 while at a significance level of 5% with dk = 50 the ttable value is 1.676 so that tcount 2.323> ttable 1.676. It can be seen that tcount> ttable, namely 2.323> 1.676 which means H0 is rejected and Ha is accepted. Based on the results of the t-test calculation, it shows that the Team Games Tournament game model can improve the visual spatial abilities of early childhood.